2021
DOI: 10.18632/oncotarget.28055
|View full text |Cite
|
Sign up to set email alerts
|

High expression of Myosin 1g in pediatric acute lymphoblastic leukemia

Abstract: Acute Lymphoblastic Leukemia (ALL) is the most frequent cancer in pediatric population. Although the treatment has improved and almost 85% of the children are cured about 20% suffer relapse, therefore finding molecules that participate in the pathogenesis of the disease for the identification of relapse and patients at risk is an urgent unmet need. Class I myosins are molecular motors involved in membrane tension, endocytosis, phagocytosis and cell migration and recently they have been shown important for deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Myosin 1g is highly expressed in B and T lymphocytes; recently we demonstrated its overexpression in high-risk pediatric ALL patients [ 8 , 18 , 23 ]. In this study, we generated monoclonal antibodies against human Myo1g, and demonstrated that the three of them could recognize the endogenous protein in normal and transformed B and T cells, and evaluated their potential use in recognizing the overexpression of Myo1g in blood samples from pediatric ALL patients as a putative biomarker.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Myosin 1g is highly expressed in B and T lymphocytes; recently we demonstrated its overexpression in high-risk pediatric ALL patients [ 8 , 18 , 23 ]. In this study, we generated monoclonal antibodies against human Myo1g, and demonstrated that the three of them could recognize the endogenous protein in normal and transformed B and T cells, and evaluated their potential use in recognizing the overexpression of Myo1g in blood samples from pediatric ALL patients as a putative biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Myo1g participates in different cell functions, particularly regulating membrane tension and Fc receptor-mediated phagocytosis, controlling cell migration and the turning angles of T and B cells, especially under antigen-limited conditions [ 13 , 14 , 16 , 26 ]. Additionally, we demonstrated that Myo1g could be used as a high-risk biomarker in pediatric ALL [ 18 ]. Leukemia treatment has improved in recent years; however, 15–20% of patients relapse [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, ATXN1 was found to be a component of Notch signaling pathway which is essential for the development and homeostasis of gastrointestinal epithelial cells [25,26]. Likewise, MYO1G as an essential regulator of membrane intension in T cells has been found involved in the lymphoblastic leukemia, and the class I myosins have been shown to be important for development and metastasis of diverse cancer types, including colorectal cancer [27,28]. Additionally, GNDF was reported to increase cell motility in colon cancer through Am J Cancer Res 2024;14(2):744-761…”
Section: An Integrated Model For Three-types Classification Of Crc Gc...mentioning
confidence: 99%